PD‐L1 expressed from tumor cells promotes tumor growth and invasion in lung cancer via modulating TGF‐β1/SMAD4 expression. Issue 9 (4th April 2022) - Chen, Ming‐Jenn; Wang, Yao‐Chen; Wang, Lee; Shen, Ching‐Ju; Chen, Chih‐Yi; Lee, Huei
Abstract: Background: Programmed death ligand‐1 (PD‐L1) has a known association with the prognosis of human cancers because of its ability to alter tumor immune surveillance via its interaction with PD‐1. We questioned whether expression of PD‐L1 in tumor cells could directly promote tumor growth and invasiveness in non–small cell lung cancer (NSCLC). Methods: Real‐time reverse transcription‐polymerase chain reaction (RT‐PCR) was performed to evaluate PD‐L1 messenger RNA (mRNA) expression in lung tumors. The prognostic value of PD‐L1 mRNA was assessed by Cox regression model. Transcriptional regulation of PD‐L1 by human papillomavirus (HPV) 16/18 E6 oncoprotein or by epidermal growth factor receptor (EGFR) mutation in lung cancer cells was examined by Western blot and luciferase reporter assay. The cell growth and invasion were evaluated by colony formation, soft agar growth, and Boyden chamber assay. Results: The PD‐L1 mRNA levels showed a positive association with HPV 16/18 E6 oncoprotein and with EGFR mutation in 223 surgically resected NSCLC patients. The prognostic significance of PD‐L1 was more commonly observed in patients with high PD‐L1/E6 positive and high PD‐L1/EGFR mutant tumors. Mechanistically, upregulation of PD‐L1 transcription by E6 or mutant EGFR occurred largely through the ERK‐C/EBPβ‐TLR4‐NF‐κB cascade. PD‐L1 promotes the efficacy of colony formation, soft agar growth, and cell invasion. PD‐L1 upregulates BAG‐1 to reduce transforming growth factor (TGF)‐β1 expression, and the decrease in SMAD4 because of TGF‐β1 occurs through the p53/microRNA (miR)‐224 axis. The decreases in TGF‐β1 and SMAD4 are responsible for PD‐L1‐mediated cell invasiveness. Conclusion: Induction of PD‐L1 by E6 oncoprotein or mutant EGFR through the ERK‐C/EBPβ‐TLR4‐NF‐κB cascade may promote tumor growth and invasiveness in NSCLC because of decreasing TGF‐β1 and SMAD4 expression. Abstract : Induction of PD‐L1 by E6 oncoprotein or mutant EGFR through the ERK‐C/EBPβ‐TLR4‐NF‐κB cascade may promote tumor growth and invasiveness in NSCLC because of decreasing TGF‐β1 and SMAD4 expression. Therefore, we suggest anti‐PD‐L1 immunotherapy combined with MEK/ERK inhibitors might show a clinical benefit as a treatment for NSCLC, particularly in patients with E6‐positive and/or EGFR mutant tumors.